Analisis Pengaruh Lingkungan dalam Pembangunan Ibu Kota Negara (IKN) sebagai Kejahatan Lingkungan - Malian, Deri; Diaz, Hadina Rivaldi; Yvonne, Gloria Natassja (Universitas Batanghari Jambi, 2024)
This research aims to find out what influences arise from the development of the Indonesian Capital City. The method used in this research is literature review research which involves reviewing and critically evaluating existing literature sources. Literature reviews contain descriptions of theories, findings and other research materials obtained from reference materials to serve as a basis for research. The results of the research show that with the development of the Archipelago Capital City, there are various influences that will be experienced in the future, starting from the influence of cultural differences, disrupting the ecosystem of living things that previously existed in the Archipelago Capital environment, as well as a reduction in oxygen. due to development around forest areas in the Indonesian Capital City.